Identifying and characterizing the most significant β-glucosidase of the novel species Aspergillus saccharolyticus - Sørensen, Annette; Ahring, Birgitte K; Lübeck, Mette; Ubhayasekera, Wimal; Bruno, Kenneth S; Culley, David E; Lübeck, Peter S (Canadian journal of microbiology, 2012)
The newly discovered fungal species Aspergillus saccharolyticus was found to produce a culture broth rich in β-glucosidase activity. In this present work, the main β-glucosidase of A. saccharolyticus responsible for the efficient hydrolytic activity was identified, isolated, and characterized. Ion exchange chromatography was used to fractionate the culture broth, yielding fractions with high β-glucosidase activity and only 1 visible band on an SDS–PAGE gel. Mass spectrometry analysis of this band gave peptide matches to β-glucosidases from aspergilli. Through a polymerase chain reaction approach using degenerate primers and genome walking, a 2919 bp sequence encoding the 860 amino acid BGL1 polypeptide was determined. BGL1 of A. saccharolyticus has 91% and 82% identity with BGL1 from Aspergillus aculeatus and BGL1 from Aspergillus niger, respectively, both belonging to Glycoside Hydrolase family 3. Homology modeling studies suggested β-glucosidase activity with preserved retaining mechanism and a wider catalytic pocket compared with other β-glucosidases. The bgl1 gene was heterologously expressed in Trichoderma reesei QM6a, purified, and characterized by enzyme kinetics studies. The enzyme can hydrolyze cellobiose, p-nitrophenyl-β-d-glucoside, and cellodextrins. The enzyme showed good thermostability, was stable at 50 °C, and at 60 °C it had a half-life of approximately 6 h.